Sintesis Asam 2-(2-(n-(2,6-diklorofenil)-4 fluorobenzamida)fenil)asetat sebagai Kandidat Obat Penghambat COX (siklooksigenase) - Triodora Hutahuruk; Ayik Rosita; Ika Oktavianawati (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Sodium diclofenac is a non selectif NSAID that used as an inflammatory, analgesic, and antipyretic. Several experiment about compound as a derivate sodium diclofenac has been synthesized for reduce side effect. 2-(2-(N-(2,6-dichlorophenyl)-4-fluorobenzamido)phenil)acetat acid (N4FND) is derivate of sodium diclofenac that synthesized for development of drugs. The target compound has been synthesized by benzoylation reaction between sodium diclofenac with 4-fluorobenzoylchloride. And then, the target compound has been purified using Coloumn Chromatography. The isolate was identified using 1HNMR 400 MHz and KBr FTIR. Spectra of of 1HNM 00 MHz and KBr FTIR showed that 2-(2-(N-(2,6-dichlorophenyl)-4-fluorobenzamido)phenil)acetat acid was successfully synthesized. Pure product compound form yellowish white crystals with melting point 165-1670C.